Imagining the Death of Jesus in Fourth Century Mesopotamia : A Study of Ephrem of Nisibis - Hartung, Blake, (Vigiliae Christianae, Supplements ;, 2023)
In this volume Blake Hartung explores the place of the passion and death of Jesus in the writings of Ephrem of Nisibis (ca. 307-373). The book argues that the genre of Ephrem's works (usually short poems for public performance), is key to understanding his unsystematic approach. Ephrem drew widely upon the Passion narratives and traditional motifs related to Christ's death and deployed them differently in distinct settings. Each chapter explores a key theme in Ephrem's discourse about the death of Christ in context (including anti-Judaism, the defeat of death, and economic imagery). Ultimately, Hartung urges further consideration of the role of Christ's death in early Christian thought and practice beyond the traditional confines of atonement theology.